Монтажне мислення: креативний підхід до створення відео - Карпенко, М. В.; Кулішова, Н. Є. (ХНУРЕ, 2025)
This work demonstrates the method of using modern editing techniques, such as Match Cut, sound animation transitions, which allow you to create emotionally rich and dynamic content when creating videos.
Keywords: монтажне мислення; створення відео